O povo como fiel da balança: trajetória da teoria do populismo na obra de Ernesto Laclau - Soares, Jaime de Oliveira (2010)
This research has as discusses the role that the people exercise in the formation of political identities and the construction of political speeches by political movements in Latin America: who are the people in contemporary mass society? What is the weight of its role in social and political events of national social formations in recent history? This study therefore aims to partially reconstruct the main path along the "theory of populism" in the work of academic researcher and teacher, born in Argentina and settled in England, Ernesto Laclau, with the aim of studying its core elements, besides presenting its ruptures and continuities front of historical events. Another objective, also sought, is to present part of the debate of ideas involving currently such a theory within the social sciences, presenting some of his interlocutors. We believe that these objectives are critical to the future that we can produce policy analysis about the political movements in countries (national social formations) in Latin America